2016
DOI: 10.1080/17437199.2016.1159142
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual coping, psychosocial adjustment, and physical health in youth with chronic illness: a meta-analytic review

Abstract: The results reveal that spiritual coping is an important coping strategy for paediatric patients. Consistent with findings among adults with chronic illness, negative spiritual coping puts paediatric patients at risk for psychosocial maladjustment and poorer health. Intervention research is needed to determine if targeting spiritual coping improves health and psychosocial well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 58 publications
2
25
0
Order By: Relevance
“…Moreover, they always feel the presence of God as a supernatural power and do not feel lonely when facing challenges in life (16). According to previous studies, spirituality and religion can strengthen a person against the difficulties and adversities of life (17,18). Safara et al in their study showed that spirituality can improve one's mental health (19).…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, they always feel the presence of God as a supernatural power and do not feel lonely when facing challenges in life (16). According to previous studies, spirituality and religion can strengthen a person against the difficulties and adversities of life (17,18). Safara et al in their study showed that spirituality can improve one's mental health (19).…”
Section: Introductionmentioning
confidence: 98%
“…Spirituality, support strategy and coping in the route of young people with a chronic disease and their families ( 39 ) , was praised by the participants, from the diagnosis to all the experienced stages. Faith is considered a vital element in the search for meaning in the face of the malformation; the belief that it is Gods will and/or that God believed in the strength of the family to take care of this child, mobilizes members in the face of difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Spiritual well-being is an aspect of health with diverse definitions in different cultures and religions. In this regard, experts have not yet reached a consensus on a precise definition of this important aspect of health that is closely knit-related to other aspects of health (29).…”
Section: Discussionmentioning
confidence: 99%